2022
DOI: 10.1001/jamaneurol.2022.2189
|View full text |Cite|
|
Sign up to set email alerts
|

Global Prevalence and Incidence of Tinnitus

Abstract: ImportanceTo date, no systematic review has taken a meta-analytic approach to estimating the prevalence and incidence of tinnitus in the general population.ObjectiveTo provide frequency estimates of tinnitus worldwide.Data SourcesAn umbrella review followed by a traditional systematic review was performed by searching PubMed-MEDLINE and Embase from inception through November 19, 2021.Study SelectionResearch data from the general population were selected, and studies based on patients or on subgroups of the pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(114 citation statements)
references
References 81 publications
1
70
0
1
Order By: Relevance
“…Neuroscience of tinnitus—a perceived, phantom impression of sound without an external source or stimulus—has produced a vast body of work in recent years. This condition, affecting a percentage of the population variably estimated from 4.1% to 37.2% and pooled meta‐analysis set at 14.4% (Jarach et al, 2022), is well known to particularly impact the life of professional musicians (Burns‐O'Connell et al, 2021; Schmidt et al, 2019), and musical elements can also play a role as treatment components (Pantev et al, 2012). A complex disorder caused by a combination of genetic and environmental factors, tinnitus has most recently spurred a dedicated research thread on the pertinent sex/gender differences, introducing a more detailed consideration of “Sex/(gender) as a Biological Variable” (SABV) into this domain.…”
Section: Psychopathological Psychological and Cognitive Differencesmentioning
confidence: 99%
“…Neuroscience of tinnitus—a perceived, phantom impression of sound without an external source or stimulus—has produced a vast body of work in recent years. This condition, affecting a percentage of the population variably estimated from 4.1% to 37.2% and pooled meta‐analysis set at 14.4% (Jarach et al, 2022), is well known to particularly impact the life of professional musicians (Burns‐O'Connell et al, 2021; Schmidt et al, 2019), and musical elements can also play a role as treatment components (Pantev et al, 2012). A complex disorder caused by a combination of genetic and environmental factors, tinnitus has most recently spurred a dedicated research thread on the pertinent sex/gender differences, introducing a more detailed consideration of “Sex/(gender) as a Biological Variable” (SABV) into this domain.…”
Section: Psychopathological Psychological and Cognitive Differencesmentioning
confidence: 99%
“…Patients may define their tinnitus by the limitations they experience in daily life, while others may not be bothered by their tinnitus [ 2 ]. Studies have reported highly variable tinnitus prevalence, ranging from 4% to 37% worldwide and from 9% to 29% in Europe [ 3 , 4 , 5 , 6 ]. Some authors also report tinnitus defined according to the time of its occurrence or according to the perceived distress [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…in the lack of vibration of an external elastic body, which can be perceived as subjective or objective (i.e., can be heard by an outside observer), pulsatile (e.g., most often heart rhythmic) or not [ 1 , 2 ]. According to recent data, the different forms of tinnitus have a dramatically high burden in the general population, with annual incidence in adults ranging between 1–14% (2% with severe forms) and prevalence of 10% in young adults, increasing to 14% in middle-aged adults, and peaking at 24% in older adults (around 2.3% with severe phenotype), respectively [ 3 ]. The burden of this condition has also consistently increased during the coronavirus disease 2019 (COVID-19) pandemic [ 4 ], due to direct viral injury of sensorineural hearing apparatus [ 5 ], compounded by a considerable onset of COVID-19-realted psychosocial conditions in the general population (e.g., stress, anxiety and depression) that may have worsened a pre-existing tinnitus [ 6 ].…”
Section: Introductionmentioning
confidence: 99%